Combined effects of agomelatine and 2600 MHz radiofrequency field on inflammation induced by chronic lipopolysaccharide administration - Oruc, Sinem; Gunay, Sevilay; Sirav Aral, Bahriye; Erden, Yavuz; Ozkut, Mahmud Mustafa; Ates, Kayhan; Eraslan, Ersen (Taylor & Francis Inc, 2025)
The aim of this study is to investigate the potential synergistic effects of agomelatine(AGM) and 2600 MHz radiofrequency(RF) field exposure on inflammation induced by chronic lipopolysaccharide(LPS) administration in rats. A total of 49 female Wistar albino rats were randomly divided into 7 groups(n = 7 per group): Control, Sham, LPS, LPS+AGM,LPS+RF,AGM+RF, and LPS+AGM+RF. Animals in the RF groups were exposed to a 2600 MHz field (1 h/day for 15 days). The whole-body averaged SAR was calculated to be 0.637 W/kg, while the localized SAR values were found to be 1.27 W/kg for 1 g and 0.91 W/kg for 10 g of brain tissue at a frequency of 2600 MHz. Chronic LPS administration(1 mg/kg/day for 15 days) successfully induced a systemic inflammatory state. The most significant finding was observed in plasma IL-6 levels. While AGM or RF exposure alone did not significantly alter IL-6 levels in LPS-treated animals, the combined treatment of LPS+AGM+RF resulted in a substantial and statistically significant decrease in plasma IL-6 compared to the sham group(p < 0.001). This represents a large-magnitude effect (Cohen's d = 1.59), suggesting a potent anti-inflammatory action of the combined therapy. In contrast, plasma IL-1 beta and TNF-alpha levels showed no statistically significant differences among any of the groups. In the hypothalamus, chronic LPS exposure was associated with a downregulation of MAP kinase signaling pathways (ERK, JNK), indicative of endotoxin tolerance, and with reduced NF-kappa B level. This study provides novel evidence that 2600 MHz RF, when combined with AGM, may exert a powerful anti-inflammatory effect, highlighting a potential therapeutic interaction that warrants further investigation.
Keywords: Radiofrequency fields; agomelatine; lipopolysaccharide; cytokines; intracellular signaling pathways; electromagnetic field; mobile phone